TC-BeEZ: tax computation be easy / Rani Diana Othman … [et al.] - Othman, Rani Diana; Saruji, Suzana; Abd Hamid, Nadiah; Che Lah, Muhammad Faiz Aimullah; Zamiruddin, Raudhah ‘Aqeela (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Computing tax liability for businesses always a dilemma in tax courses’ learning process. This is due to the fact that students are still in the process of grasping accounting technical issue while they need to develop deep understanding on tax legal aspect of allowable and disallowable expenses under Section 33, 34 and 39, Income Tax Act 1967. Inadequate knowledge in differentiating accounting treatment as compared to taxation treatment has unable the student to score good marks in this topic. At the same time, lacking of strong foundation in this area tend to affect the performance and the quality of tax services among tax practicing industry. Taking this into consideration, a collaborative project is initiated to develop an ‘advanced Excel-formatting worksheet’ to ease the learning process and help the student to understand the concept of computing Adjusted Business Income in an exciting and easy way. TC-BeEZ is developed to bridge the academic’s theory and industry’s practicing element by establishing an easy and effective learning method towards computing tax liability of business entities. More importantly, adequate understanding on both accounting and legal concept of tax provision will provide the tax industry with higher number of future competent tax practitioner and at the same time ensuring an adequate tax revenue collection for the country.